2023
DOI: 10.1039/d2nr06669f
|View full text |Cite
|
Sign up to set email alerts
|

Screen-printed highly stretchable and stable flexible electrodes with a negative Poisson's ratio structure for supercapacitors

Abstract: Flexible power sources are crucial to developing flexible electronics systems, nonetheless the current poor stretchable and stable of flexible power sources hinder their application in such devices. Accordingly, the stretchability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Silver serpentine electrode is one of the simplest fabrication methods like gold serpentine electrodes. [129] It gives the flexibility to endure skin strain with cost effectiveness. [130] Niu et al reported the low-cost silver e-tattoo electrodes for the measurement of ECG and EEG.…”
Section: Silver Metal-based Electrodesmentioning
confidence: 99%
“…Silver serpentine electrode is one of the simplest fabrication methods like gold serpentine electrodes. [129] It gives the flexibility to endure skin strain with cost effectiveness. [130] Niu et al reported the low-cost silver e-tattoo electrodes for the measurement of ECG and EEG.…”
Section: Silver Metal-based Electrodesmentioning
confidence: 99%
“…The observation that the electrical response output force of artificial muscles has a greater correlation with the number of movable ions inside the actuator film has been confirmed in previous work. Therefore, it was important to perform electrochemical experiments on artificial muscles [27]. Five sets of cyclic voltammetry experiments with different groups of artificial muscles were performed (equipment model: CHI600E, scanning rate 20 mV s −1 ) and the specific capacitance of each set of samples was calculated as follows:…”
Section: Electrochemical Experimentsmentioning
confidence: 99%
“…As electronics technology gradually matures, flexible electronic devices that can be attached to curved surfaces are under rapid development. In areas such as health monitoring, human-computer interaction, flexible displays, and printed electronics, researchers have invested heavily. Developing flexible electronic technology can make living more convenient, but most of the flexible electronic devices are made of nondegradable synthetic polymers, which will lead to an increase in e-waste when the devices are discarded.…”
Section: Introductionmentioning
confidence: 99%